الأنساق الثقافية في قصيدة بطاقة هوية للشاعر محمود درويش - مداني, علاء; قدور, الخنساء; معوش, سميرة; معوش, وفاء (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى التعرف على منهج النقد الثقافي ومعرفة آلياته في قراءة و استنطاق النصوص والخطابات، كما نسعى من خلالها إلى تطبيق هذه الآليات على قصيدة "بطاقة هوية" للشاعر "محمود درويش" للكشف عن الأنساق الثقافية الظاهرة والمضمرة فيها، من خلال ما تحمله من خصائص بلاغية جمالية، انطلاقا من الإجابة عن الإشكالية الآتية: ماهي الأنساق الثقافية التي تضمنتها قصيدة "بطافة هوية" "للشاعر محمود درويش"؟، إذ تطرقنا في بحثنا هذا إلى مفهوم النقد الثقافي والنسق الثقافي، وكذا التعريف بالشاعر وقصيدته لتكون لنا بعد ذلك وقفة مع قراءة الأنساق الثقافية في هذه القصيدة. This study aims to identify the approach of cultural criticism and to know its mechanisms in reading and interrogating texts and discourses. We also seek through it to apply these mechanisms to the poem “Identity Card” by the poet “Mahmoud Darwish” to reveal the apparent and implicit cultural patterns in it, through the meanings it contains. Aesthetic rhetorical characteristics, based on the answer to the following problem: What are the cultural patterns included in the poem “With Identity” by the poet Mahmoud Darwish? In this research, we touched on the concept of cultural criticism and the cultural pattern, as well as introducing the poet and his poem, so that we can then pause with Reading the cultural patterns in this poem.
أدب عربي حديث ومعاصر
Keywords: الأنساق الثقافية - قصيدة – بطاقة هوية – محمود درويش; cultural patterns - poem - identity card - Mahmoud Darwish